Method of suppressing jitter instability during electrospinning: Insulator auxiliary method. (2nd January 2018) - Wei, Wang; Wei, Qiang; Ya-nan, Yang
ABSTRACT: In this paper, we first analyze the motion process of steady-state jets based on the conservation of momentum and establish the control equations. Then we propose an electrospun nanofibers method to increase the acrylic plastic blocks in space, and use the finite element analysis software COMSOL Multiphysics 5.0 to establish the geometrical Model. For the increase of the width and quantity of acrylic plastic block, the distribution of field intensity corresponding to 5 cm and 13 cm below the needle is analyzed. It is found that the field strength increases with the increase of the width of the acrylic block, and the field strength reaches the maximum when reaching 8 cm, which is 7.19 × 10 4 V/m and 5.62 × 10 4 V/m respectively. When the width is 8 cm, two pieces of acrylic plastic block of the same width are made to make the acrylic plastic frame. At this point, the field strengthat 5 cm and 13 cm below the needle continues to increase, and the values are 8.32 × 10 4 V/m and 6.29 × 10 4 V/m respectively.